Epidemiologic studies of occupational cancer as related to complex mixtures of trace elements in the art glass industry. - Wingren, Gun; Axelson, Olav (Scandinavian Journal of Work, Environment & Health, 1993)
In the art glass industry workers run increased risks of dying from several types of cancer, cardiovascular diseases, and cerebrovascular diseases. This paper considers the diseases of glass workers in relation to exposure to particular elements, a high degree of correlation being found for some of them. Case-referent evaluations showed an association between stomach cancer and exposure to a mixture of elements, namely, arsenic, copper, nickel, and manganese, and to some extent also to lead and chromium. For colon cancer, a clearly increasing trend in risk was seen with increasing use of antimony, and to some extent also with increasing use of lead, the two elements being strongly correlated. For lung cancer no obvious correlation with any metal could be found. In addition, the risk for death from cardiovascular disease was fairly evenly distributed, although slightly more related to increasing consumption of the strongly correlated metals nickel and copper.